Emerging Enterococcus isolates in postoperative endophthalmitis by selection pressure of fluoroquinolones: an 11-year multicenter and experimental study - Jiyeun Kate Kim; Ki Yup Nam; In Young Chung; Woo Jin Jeung; Yoon Hyung Kwon; Jung Min Park; Yong Seop Han; Ji Eun Lee; Ik Soo Byon; Sung Hu Park; Hyun Wong Kim; Kang Yun Park; et al. (Emerging Microbes and Infections)
Postoperative endophthalmitis (PE) is the devastating complication that frequently results in vision loss. Recently, enterococcus have emerged as a major cause of PE in several countries and resulted in poor visual outcome. However, the reason remains elusive. We investigate whether selection pressure of fluoroquinolone exerts effects on microorganism profiles isolated from PE. Medical records of patients who were diagnosed with PE at eight resident training institutions between January 2004 and December 2015 were reviewed. The most common isolate was Enterococcus faecalis (28.0%), followed by Staphylococcus epidermidis (18.6%) and other coagulase negative Staphylococci (7.6%). However, the rates of E. faecalis isolated from conjunctival microbes were 6.2% (16/257) and their resistance to fluoroquinolones was higher than those of S. epidermidis. In vitro and in vivo co-culture models of E. faecalis and S. epidermidis were established for survival assays after administration of fourth-generation fluoroquinolone. In in vitro co-culture model, the survival assay of E. faecalis and S. epidermidis against the treatment of moxifloxacin showed that E. faecalis survived significantly better than S. epidermidis in the presence of moxifloxacin 1 µg/mL and more. In in vivo co-culture model, E. faecalis survived significantly better than S. epidermidis after topical treatment of moxifloxacin (5 mg/mL). E. faecalis has been the most common causative strain of PE in Korea. We suggest that the increase of E. faecalis in PE could be associated with the selection pressure of fourth-generation fluoroquinolone.Summary: Enterococcus spp. have emerged as a leading causative strain of postoperative endophthalmitis in 11-year clinical data. We suggest that the increase of Enterococcus spp. is associated with the selection pressure of fourth-generation fluoroquinolone.